DAMPAK PROBLEMATIKA PAI (PENDIDIKAN AGAMA ISLAM) DI SEKOLAH UMUM - Puspita Ega Melinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Islamic Religious Education (PAI) holds a strategic role in shaping the character, morality, and religious awareness of students, particularly in public schools that are increasingly influenced by modernization and secular cultural currents. However, its implementation continues to face various challenges that hinder its effectiveness. Based on the analysis presented in this paper, these challenges include internal issues such as limited instructional time, low student motivation, insufficient teacher competence, and a lack of supporting facilities. External challenges involve weak family involvement, the influence of global secular culture, unsupportive school environments, and policies that do not adequately prioritize religious activities. This study aims to examine the forms of PAI-related problems in public schools, analyze their impact on students’ spiritual and moral development, and propose strategic solutions to strengthen PAI implementation. Employing a qualitative approach through literature review and document content analysis, the study reveals that these challenges lead to declining religious awareness, reduced motivation for worship, value disorientation, and identity crises among students. The findings emphasize the need to enhance teacher professionalism, promote innovative and technology-based instructional methods, optimize religious extracurricular programs, strengthen collaboration between schools, families, and communities, and reinforce curriculum policies that support religious education. This study contributes to the development of an integrative and adaptive PAI learning model suited to the challenges of 21st-century education.